The Effect of a Training Program Based on Artificial Intelligence Techniques According to Physical Fitness Level Using Motion Sensors (Accelerometer & Gyroscope) on Developing Explosive Power and Passing and Shooting Skills Among Young Basketball Players - Talab , Doaa (Journal of Physical Education, 2025)
Basketball training no longer relies solely on coaches’ personal experience or traditional on-field repetition. Instead, it has undergone a qualitative shift thanks to the integration of artificial intelligence (AI) technologies, which have become effective tools in analyzing performance and guiding training with precision and objectivity. In light of rapid technological advancements, it is now possible to obtain accurate motion data that surpasses human observational capabilities, enabling the design of individualized training programs tailored to each player’s needs. The research problem stems from field observations indicating a decline in the performance level of several young basketball players during matches in the Iraqi league. This decline is attributed to difficulties in maintaining a high level of physical and technical performance throughout the game, especially during extended periods of play or under conditions that require sustained high effort. This leads to a drop in passing accuracy and weaker performance in one-on-one situations.In response to these challenges, the researcher designed an innovative training program based on AI technologies, utilizing performance sensors (Accelerometer & Gyroscope) to assess and analyze each player’s physical level and adapt training accordingly.The study adopted an experimental methodology using two groups: an experimental group that underwent the AI-based training program, and a control group that trained using traditional methods. The program lasted six weeks, with two training sessions per week. The results clearly demonstrated the superiority of the experimental group in developing speed endurance, as well as improving performance in essential basketball skills such as passing and shooting. These findings highlight the effectiveness of integrating artificial intelligence and motion analysis in enhancing the athletic performance of young basketball players